2020
DOI: 10.1111/1751-7915.13590
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the copper sensitivity of microorganisms by restricting iron supply, a strategy for bio‐management practices

Abstract: Pollution by copper (Cu 2+) extensively used as antimicrobial in agriculture and farming represents a threat to the environment and human health. Finding ways to make microorganisms sensitive to lower metal concentrations could help decreasing the use of Cu 2+ in agriculture. In this respect, we showed that limiting iron (Fe) uptake makes bacteria much more susceptible to Cu 2+ or Cd 2+ poisoning. Using efflux mutants of the purple bacterium Rubrivivax gelatinosus, we showed that Cu + and Cd 2+ resistance reli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 67 publications
0
12
1
Order By: Relevance
“…Nevertheless, if Cd 2+ or Cu + metallates Fur in vivo and allows binding to the Fur box, we may then expect a repression of the iron uptake systems and induction of the Fe‐Sod. Our results showed, however, an induction of Fe‐Sod and the FbpABC iron uptake system (Steunou et al , 2020b), which rather suggest that Fur is unloaded in the presence of Cd 2+ or Cu + .…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Nevertheless, if Cd 2+ or Cu + metallates Fur in vivo and allows binding to the Fur box, we may then expect a repression of the iron uptake systems and induction of the Fe‐Sod. Our results showed, however, an induction of Fe‐Sod and the FbpABC iron uptake system (Steunou et al , 2020b), which rather suggest that Fur is unloaded in the presence of Cd 2+ or Cu + .…”
Section: Discussioncontrasting
confidence: 62%
“…Therefore, in these bacteria, there is no other choice but to express SodB in spite of the putative iron limitation status. To corroborate this hypothesis, we have shown that like iron starvation, Cu + and Cd 2+ excess induced iron uptake system as attested by the accumulation of the iron‐binding protein FbpA in the periplasm of R. gelatinosus (Steunou et al , 2020b). The induction of Sod in the ATPase mutants is therefore indirect and is probably the consequence of iron homoeostasis dysregulation by excess Cd 2+ or Cu + .…”
Section: Discussionmentioning
confidence: 82%
“…Induction of SodB expression in the cadA strain suggests an increase in ROS production or a dysregulation of iron homeostasis since SodB is known to be regulated by Fur regulator in bacteria. Together with the degradation of solvent exposed [4Fe-4S] cluster from key metabolic enzymes, iron homeostasis dysregulation and ROS should be considered to account for the Cd 2+ toxicity in the cadA strain (Steunou et al, 2020b).…”
Section: Discussionmentioning
confidence: 99%
“…The observed changes in metal levels could partly explain the observed transcriptional response to FZ and DOC. For example, copper excess has been reported to degrade Fe-S clusters, block Fe-S cluster assembly, and stimulate an iron starvation response in E. coli and other bacteria ( 33 36 ). Therefore, copper toxicity could be a contributing factor that results in an iron starvation response to DOC or FVD.…”
Section: Resultsmentioning
confidence: 99%